Recurrent Cystitis in Women-A Real-World Analysis of Bacteria Spectrum and Resistance Situation for Calculated Therapy - Philipp J. Spachmann; Maximilian Radlmaier; Stefan Denzinger; Maximilian Burger; Johannes Breyer; Wolfgang Otto; Marco J. Schnabel; Daniel Vergho (MDPI AG, 2024)
Recurrent cystitis in women represents an everyday challenge; however, little to no data regarding this population are available. This study aimed to evaluate this collective with respect to a rational calculated antibiotic therapy. Urine cultures and antibiograms from a urological office were retrospectively evaluated from patient data collected between January 2017 and June 2019. The evaluation was conducted using SPSS ©. In total, 84 female patients, who were aged between 18 and 87 years old (median 60 years), suffered from recurrent cystitis. Escherichia coli was found in 53.9% of cases, Staphylococcus aureus and enterococci were each found in 6.7%, and Proteus spp. and Streptococcus agalactiae were each found in 5.6%. The resistance levels to ciprofloxacin (CIP), trimethoprim-sulfamethoxazole (TRS), nitrofurantoin (NIT), and nitroxoline (NOX) were 18.2%, 30.7%, 16.1%, and 12.5% in the tested cases, respectively. Regarding E. coli, resistance to CIP, TRS, and NIT was found in 17.8%, 25%, and 4.2% of the tested cases, and no resistance to NOX was found. The resistance level to CIP was in a tolerable range of <20% in the overall cohort and the E. coli subgroup. More than a quarter of the bacteria were resistant to TRS. The low resistance rates for NIT and NOX are remarkable, promoting the use of these substances if they are not yet used.